The Smart City Implementation and Development Model in Realizing Bureaucratic Reform in the Local Government of Cimahi City - Titin Rohayatin; Zaenal Abidin AS; Harky Ristala (UIN Sunan Gunung Djati, 2023)
This study delves into the implementation and development of a Smart City model as a strategic approach by the Regional Government to achieve bureaucratic reform. The aim is to address challenges associated with inefficient service systems, lengthy processes, organizational structures, and bureaucratic placements that hinder effective government management. Focused on Cimahi City's urban development strategy, the Smart City concept integrates the Internet of Things (IoT) and information and communication technology (ICT) to optimize city assets, enhance law enforcement, streamline government agency information systems, and improve community services. However, despite its potential, the government's Smart City strategy faces obstacles, including server errors, login difficulties, frequent application loading, cumbersome display interfaces, and unresponsive buttons. In response, this research proposes the TRSCM model as a framework for the effective implementation and development of Smart City initiatives, aiming to overcome barriers and contribute to the realization of meaningful bureaucratic reform in government organizations.